Secondary Acute Myeloid Leukemia in a One-Year-Old Girl Diagnosed with JAK2-V617F Mutation Positive Myeloproliferative Neoplasm. (18th March 2014) - Woods, Gary M.; Bajwa, Rajinder P. S.; Kahwash, Samir B.; Guinipero, Terri
Abstract : Myeloproliferative neoplasms (MPNs) are a group of clonal disorders characterized by hyperproliferation of hematologic cell lines and have been associated with tyrosine kinase JAK2-V617F mutations. Secondary acute myeloid leukemia (sAML) is a known complication of JAK2-V617F+ MPNs and bears a poor prognosis. Although the evolution of a JAK2-V617F+ MPN to a mixed-lineage leukemia has been reported in the pediatric population, no evolutions into sAML have been described. We present a case of a one-year-old girl diagnosed with JAK2-V617F+ MPN with evolution into sAML. Despite initial morphologic remission, she eventually relapsed and succumbed to her disease.